Lipid Phases and Cell Geometry During the Cell Cycle of Streptococcus pneumoniae - Calvez, Philippe; Jouhet, Juliette; Vié, Véronique; Durmort, Claire; Zapun, André (Frontiers in Microbiology, 2019)
The coexistence of different lipid phases is well known in vitro, but evidence for their presence and function in cellular membranes remains scarce. Using a combination of fluorescent lipid probes, we demonstrate the coexistence of liquid and gel phases in the membrane of Streptococcus pneumoniae, where they are localized to minimize bending stress in the ellipsoid geometry defined by the cell wall. Gel phase lipids with high bending rigidity are spontaneously organized at the equator where curvature is minimal, thus marking the future division site, while liquid phase membrane maps onto the oblong hemispheres. In addition, the membrane-bound cell wall precursor with its particular dynamic acyl chain localizes at the division site where the membrane is highly curved. We propose a complete “chicken-and-egg” model where cell geometry determines the localization of lipid phases that positions the cell division machinery, which in turn alters the localization of lipid phases by assembling the cell wall with a specific geometry.